Attachment Competences in Children With ADHD During the Social-Skills Training and Attachment (SOSTRA) Randomized Clinical Trial. (October 2015) - Storebø, Ole Jakob; Skoog, Maria; Rasmussen, Pernille Darling; Winkel, Per; Gluud, Christian; Pedersen, Jesper; Thomsen, Per Hove; Simonsen, Erik
Objective: To investigate the effects of social-skills training and a parental training program on children with ADHD as measured by the children's attachment competences.Method: The SOSTRA trial is a randomized, parallel-group, outcome-assessor-blinded, superiority trial evaluating 8 weeks social-skills training and parental training plus standard treatment versus standard treatment alone for 8- to 12-year old children with ADHD.Results: There were no significant differences in attachment competences at 6 months between the experimental ( n = 25) and the control ( n = 22) groups (odds ratio = 1.06, 95% confidence interval = [0.31, 3.58], p = .91). In total, 17 children (36%) changed their entry status, 1 (2%) from secure to insecure attachment, while 16 (34%) changed from insecure to secure attachment.Conclusion: The experimental treatment does not seem to affect attachment competences compared with standard treatment alone. Children in the SOSTRA trial improved their attachment competences significantly at 6-month follow-up.